Role of agriculture credit in enhancing livelihood of farmers: Evidence from Northern Tamil Nadu - Kiruthika S; Kiran S (International Journal of Social Sciences Review, 2023)
Agricultural credit plays a vital role in improving productivity and efficiency in the farming sector. The pattern and extent of loan utilization and crop loan diversification was analyzed with sample farmers from K.V. Kuppam and Gudiyatham blocks of Vellore district where 45 farmers (borrowers and non-borrowers) from each block were selected respectively by multistage random sampling method.  The majority of the sample respondents are educated where 56.36 per cent of borrowers and 45.71 per cent of non-borrowers have secondary education. The major crops grown by the sample farmers were papaya, mango, and coconut. Major sources of credit for farmers were found to be co-operative banks (52.10 %) followed by relatives and friends (26.99 %), commercial banks (12.26 %) and money lenders (8.65%). An 83.40% of loan amount was utilized for the crop production, 11.41% was used for other farm enterprises and 5% was used for household consumption. About 86.07 per cent of borrowers used the loan amount for crop production while 8.93 per cent of loan amount is used for other farm production purpose and 7.23 per cent is used household purpose. Technical efficiency scores were higher for borrowers (0.79) when compared with non-borrowers (0.63). The results of Tobit regression show that crop loan availed by the farmers, gross cropped area and net irrigated area has a significant effect on the technical efficiency of farm business. Availing loans has helped farmers to adopt new technologies and increased the technical efficiency of farming.